Patricia Gamboa COVID-19 Wedding Photograph - Gamboa, Patricia::::::::: (2022)
A photograph of MARA (Master's in Archives and Records Administration) student Patricia Gamboa's wedding in Bel Vino Winery in Temecula, California during the COVID-19 pandemic.